The possible impact of solar activity on the summer temperature distribution over Eurasia - Lu, Wei; Xiao, Ziniu; Feng, Xueshang (Frontiers in Earth Science, 2023)
In this study, observations and reanalysis datasets are used to investigate the response of summer temperature distribution in Eurasia to solar activity. Based on the empirical orthogonal function (EOF) and correlation analysis, the possible link between the second pattern of summer temperature over Eurasian land (0-180°E and 20°N-80°N) and solar activity is revealed. The corresponding time series of the second pattern has an 11-year significant solar periodicity. The tripolar temperature distribution is similar to the correlation maps between the temperature and sunspot number (SSN). Combining the temperature distribution pattern and correlation maps, Central Asia (50°E-90°E and 30°N-60°N) is the key response region, different from the other areas of Eurasia. The temperature of Central Asia shows a weak but significant negative correlation with SSN. Further analysis of atmospheric circulation reveals the mechanism. The solar-induced cyclonic and negative geopotential height anomalies in Central Asia weaken the high-pressure ridge on the southwest side and strengthen northwesterly winds. At the same time, with the increase in the cloud cover and the decrease of shortwave radiation, the temperature is lowered. Due to the impact of solar activity, the upper atmosphere over Eurasia forms a wave train-like structure, resulting in a tripolar temperature distribution pattern. On the other hand, the 21-year sliding correlation results indicate the connection between solar activity and the temperature in Central Asia was strong and decadal stable until 1980. However, the temperature and atmospheric circulations in high latitudes come to be more sensitive to solar activity after 1980. Solar activity still can be considered a non-negligible factor in the prediction of the summer temperature in Eurasia.